PsycEXTRA Dataset 2004
DOI: 10.1037/e620452007-001
|View full text |Cite
|
Sign up to set email alerts
|

Offenders of the Future?: Assessing the Risk of Children and Young People Becoming Involved in Criminal or Antisocial Behaviour

Abstract: The views expressed in this report are the author's and do not necessarily reflect those of the Department for Education and Skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Broadly, a risk factor infl ates the likelihood that a person will experience some negative outcome and a protective factor reduces it, but relationships between risk and protective factors can be very complex, and the balance of risk and protective factors in the lives of young people seems more important in determining outcomes than single risk factors (Rutter, 1999 to infl uence outcomes (McCarthy et al, 2004). All three models have strengths and weaknesses (e.g.…”
Section: A Risk and Protection-focused Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Broadly, a risk factor infl ates the likelihood that a person will experience some negative outcome and a protective factor reduces it, but relationships between risk and protective factors can be very complex, and the balance of risk and protective factors in the lives of young people seems more important in determining outcomes than single risk factors (Rutter, 1999 to infl uence outcomes (McCarthy et al, 2004). All three models have strengths and weaknesses (e.g.…”
Section: A Risk and Protection-focused Approachmentioning
confidence: 99%
“…All three models have strengths and weaknesses (e.g. the additive model fails to take account of risk and protective factors which are not diametrically opposed to one another), and it has been suggested that models of resilience need to be based on the premise that all three characterisations have value (for a review, see McCarthy et al, 2004). …”
mentioning
confidence: 99%
“…These factors have been found to increase the risk that young people will become involved in criminal or antisocial behaviour (McCarthy et al, 2004). These factors have been found to increase the risk that young people will become involved in criminal or antisocial behaviour (McCarthy et al, 2004).…”
Section: Intensive Individualised Therapymentioning
confidence: 99%
“…The essential meaning of ecological theory (Berger, McBreen, & Rifkin 1996;Bronfenbrenner, 1986;Fraser, 1997;Ungar, 2011), as well as the theory of risk and resilience (Kirby & Fraser, 1997;McCarthy, Laing, & Walker, 2004), is based on respect and fulfilment of human rights, with an emphasis on child rights. In view of the strong need to act on the local level, we may conclude that it is precisely in local communities that the Convention should be implemented, taking into account the specific needs and problems of these communities.…”
Section: Introduction To the Research Problemmentioning
confidence: 99%